Clearing the air: Expression of nitrous oxide reductase from Pseudomonas stutzeri in transgenic tobacco - Staebler, Julianne Marie (University of Ottawa (Canada), 2006)
As atmospheric concentrations of N2O, a potent greenhouse gas and destructor of ozone, continue to increase, it is important to explore a range of solutions for this issue. The bacterial enzyme responsible for catalyzing the final step of the denitrification pathway, conversion of N 2O to N2, is nitrous oxide reductase (N2OR). It is the aim of this study to produce model tobacco plants expressing the nitrous oxide reductase gene (nosZ) with the ultimate goal of supplying additional N2OR to the plant-microbial-soil environment for more efficient reduction of N2O and mitigation of agricultural N 2O emissions. Two nitrous oxide reductase expression cassettes under the control of (1) the d35S constitutive promoter and, (2) the rolD root-specific promoter were constructed and used to transform Nicotiana tabacum tissue. Integration and expression of the nosZ transgene in T0 and T1 generation plants was demonstrated by PCR and RT-PCR. Production of recombinant N2OR in T0 plants was shown by western immunoblot.
Keywords: Chemistry, Biochemistry.